Resolution of Conflicts between Silat Colleges in The Sragen Region From a Criminal Law Perspective - Angga Maghrifin Suryanto; Muchamad Iksan (Universitas Muhammadiyah Surakarta, 2023)
The rise of violent conflict between silat schools, one of which is the Setia Hati Terate Brotherhood and the Indonesian Silat Boys Family Association (IKSPI)